Kontroversi Asuransi di Indonesia: Telaah Fatwa Majelis Ulama Indonesia (MUI) tentang Badan Penyelenggara Jaminan Sosial (BPJS) - Husni Mubarrak (TSAQAFAH, 2016)
This study aims to discuss on The Fatwa of The Council of Indonesian Ulama (MUI) on Health Insurance (BPJS) in 2015 which has arousing various different opinions either among elite or civilians in Indonesia. As the adviser for the Government of Indonesia in terms of religious issues, MUI questioned about the validity and appropriateness of the BPJS practice in concordance with the Islamic sharia law. At least, there are three issues which underlie the formulation and the publication of the fatwa: ranging from conformity concepts and practices of BPJS with legislation and sharia principles; what alternative solutions that can replace the presence of BPJS if it proved not qualified of sharia compliant; as well as the determination of 2% motive penalty for late payment of participant contributions, would it not contravene the sharia law? This fatwa, however, is in line with previous fatwa which issued by MUI in year 2001 on Guideline for Islamic Insurance. In MUI’s view, the operational system of BPJS still shackled within the framework of conventional insurance. By using ‘aqd mu’âwadah and presenting a pattern of relations “insurer-insured” in the management of handling BPJS insurance, not guarantee it is free from gambling, uncertainty, usury elements, which is strongly opposed to Islamic sharia law, and therefore, the concept of takâful within sharia framework as referred in the fatwa of MUI in 2001 on Guidelines for Islamic Insurance, is offered as an alternative solution formula in justice and welfare insurance for all citizens, especially for Muslims.